MAKNA SIMBOL TARI TELU SERANGKAI PADA MASYARAKAT KARO - Siska Ernita Batubara (Gesture: Jurnal Seni Tari, 2015)
This study discusses the Triad Telu Serangkai dance in the village of Karo Seberaya which aims to determine the meaning of the symbol of dance TeluSerangkai Triad. To discuss the above research purposes used the theory related to the topic ofresearch, such as the theory of meaning from Anderson in FX translation Widaryanto Anya Peterson (2001: 211-212), the theory of the symbol of Sumandiyo Hadi in his Sociology of Dance (2005: 22). Methodology The study presented in this research use descriptive qualitative data collection techniques done with literature study, observation, interviews, documentation. The research was used to discuss the Triad Telu Serangkai dance for two months, from June to August 2015. The research location is the village of the District Seberaya Tigapanah Karo. Based on research that has been done, the symbol of the dance are the Ones Telu Serangkai young romance in the Karo people. The meaning of the symbol of romance is derived from every movement made, namely: the motion of respect, motion sada tan, motion tan erputar, motion tan datas bara, motion ngelegi pudun, motion mulih, the garment worn by the female dancers, namely: hoods, rudang-rudang , Langge-Langge, kebaya, and songket, clothing that is used by the male dancers, namely: headdress-headdress, twisted-twisted, clothing, canoes, and pants, as well as floor pattern, ie forming two rows.